Introduction of Dwarf Elephant Grass (Pennisetum purpureum cv. Mott) and Annual Legumes in the Disused Limestone Mining in Karst Gombong Area, Central Java, Indonesia - Doso Sarwanto; Sari Eko Tuswati (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
The aim of this research was to revegetate the disused limestone quarry by introducing dwarf elephant grass (Pennisetum purpureum cv. Mott) and annual legumes such as peanuts (Arachis hypogaea L.), soybeans (Glycine max), cowpeas (Vigna unguiculata) and mung beans (Vigna radiata). The study was conducted experimentally in a disused limestone quarry applying Completely Randomized Design. The research method used was experimental in disused limestone mining in karst Gombong area applying Completely Randomized Design (CRD). Treatment consisted of 6 planting methods with 4 replicates. The 6 treatments research were the followings: RO: Single planting of dwarf elephant grass, R1: Single planting of dwarf elephant grass + 1.5 kg/m2 goat compost, R2: Mixture Planting of dwarf elephant grass + legume peanuts + 1.5 kg/m2 goat compost, R3: Mixture planting of dwarf elephant grass + legume soybeans + 1.5 kg/m2 goat compost, R4: Mixture planting of dwarf elephant grass + legume cowpeas + 1.5 kg/m2 goat compost and R5: Mixture planting of dwarf elephant grass + legume mung beans + 1.5 kg/m2 goat compost. The measured response variables were plant’s height, fresh yield, dry matter yield and crude protein content of dwarf elephant grass aged 8 weeks. The result showed that the addition of goat compost and the planting method of annual legumes on the disused limestone quarry had highly significant influence (P<0.01) on the increase productivity and quality of dwarf elephant grass. The best method of planting dwarf elephant grass (Pennisetum purpureum cv. Mott) on disused limestone mining in karst Gombong area is mixture planting with soybean legumes (Glycine max) and adding the 1.5 kg/m2 goat compost.